2021
DOI: 10.3389/fonc.2021.661184
|View full text |Cite
|
Sign up to set email alerts
|

Pinocembrin Inhibits the Proliferation and Metastasis of Breast Cancer via Suppression of the PI3K/AKT Signaling Pathway

Abstract: The survival rate of breast cancer (BC) patients remains poor, thus the identification of safe and effective new drugs is crucial to improve therapeutic outcomes and overall survival. Pinocembrin (PCB), a pharmacologically active ingredient of Pinus heartwood, Eucalyptus, Euphorbia, Populus, and Sparattosperma leucanthum, has been widely applied for the treatment of various diseases and possesses anticancer activities. In vitro assays were performed to investigate the antiproliferation and antimetastasis activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…Some other polyphenols have also proven effective as anti-metastatic agents. Pinocembrin, one of the major water-insoluble flavonoids in propolis, inhibited EMT and metastasis by preventing NF-κB translocation to MMP promoter sites [ 385 , 386 ]. Furthermore, at non-cytotoxic concentrations, pinocembrin suppressed the TGF-β1-induced cell-matrix adhesion, invasion, and migration of human retinoblastoma Y-79 cells.…”
Section: Antitumor Activity Of Propolis and Its Polyphenolic/flavonoi...mentioning
confidence: 99%
“…Some other polyphenols have also proven effective as anti-metastatic agents. Pinocembrin, one of the major water-insoluble flavonoids in propolis, inhibited EMT and metastasis by preventing NF-κB translocation to MMP promoter sites [ 385 , 386 ]. Furthermore, at non-cytotoxic concentrations, pinocembrin suppressed the TGF-β1-induced cell-matrix adhesion, invasion, and migration of human retinoblastoma Y-79 cells.…”
Section: Antitumor Activity Of Propolis and Its Polyphenolic/flavonoi...mentioning
confidence: 99%
“…In silico studies predicted that the analog BP might be a better inhibitor of the CYP1A2 enzyme than DYRK1A is. Studies have found that an antioxidant molecule named Pinocembrin also have potential antiproliferation activity against breast cancer cells [ 49 ], and also was found to be a CYP1A2 inhibitor [ 50 ]. From the results obtained in this study, we can strongly suggest that BP and EP action resembles the mechanism of action of Pinocembrin by having an antioxidant potential, and they possibly could bind to CYP1A2, thus exerting anticancer activity.…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that AKH mainly contains chalcones and diarylheptanoids. Pinocembrin exerts anti-inflammatory, anti-bacterial and anticancer effects ( 47 , 48 ). Studies have shown that pinocembrin inhibits the proliferation, migration and invasion of breast cancer cells at non-cytotoxic concentrations by inhibiting the STAT3 signaling pathway ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pinocembrin exerts anti-inflammatory, anti-bacterial and anticancer effects ( 47 , 48 ). Studies have shown that pinocembrin inhibits the proliferation, migration and invasion of breast cancer cells at non-cytotoxic concentrations by inhibiting the STAT3 signaling pathway ( 48 ). Cardamonin is the main flavonoid derived from AKH and exerts anti-proliferative effects against various cancer cells ( 49 ).…”
Section: Discussionmentioning
confidence: 99%